نشر تعليمات القرآن وعلومه بمنطقة السند: الشيخ محمد إبراهيم السرهندي نموذجا: Promotion of Quran and Its Sciences in Sindh: A Case Study of Muhammad Ibrahim Sarhindi (Al Basirah, 2024)
Muslim scholars have given remarkable importance to the Qur’an, deeply focusing on its study, memorization and interpretation across the world. Religious scholars of Sindh Region are also among the famous scholars in the world. They have been serving Islam since it’s advent in Sindh region and that’s why Sindh was awarded title of “Bab Ul Islam”. Among these scholars, the Sarhindi family who migrated from Afghanistan, served Qur’an and its sciences in the above-mentioned region quite well. This family and its religious prominent figures and scholars achieved a great repute in Islamic Studies. Those who provided academic services to Qur’an are Shaikh Abdurrahman 1315AH, worked on Tafseer e Jalalain and Shaikh Muhammad Hasan 1365 AH who wrote 28 books, some of them are related to Qur’an and its sciences, i.e. Qawaed-ut-tajweed and Lughat ul Qur’an etc. and Shaikh Abdullah Jan Shah Agha 1393 AH who wrote 37 books, some of them are about Qur’an and its sciences i.e. Mukhzin Ul Uloom Fil Qira’at etc. and Shaikh Muhammad Ibrahim 1432 AH, authored 20 books, including some of them are about Qur’an and its sciences i.e. Huqooq Ul Qur’an, and Shaikh Abdul Waheed who translated the Qur’an into Sindhi language which is available in audio CDs too. This research revolves around the efforts of Sheikh Muhammad Ibrahim Sarhindi in the field of the Quran and its sciences. It will cover his biography, introduction to his books, his efforts for religious schools and preaching Islam and his deep connection with the Qur’an and its sciences.
Keywords: Quranic Studies; Quran in Sindh; Quranic Sciences in Sindh; Sindhi Scholars; Sarhindi Family